Exploring ethical frontiers of visual methods. (December 2014) - Howell, Catherine; Cox, Susan; Drew, Sarah; Guillemin, Marilys; Warr, Deborah; Waycott, Jenny
Visual research is a fast-growing interdisciplinary field. The flexibility and diversity of visual research methods are seen as strengths by their adherents, yet adoption of such approaches often requires researchers to negotiate complex ethical terrain. The digital technological explosion has also provided visual researchers with access to an increasingly diverse array of visual methodologies and tools that, far from being ethically neutral, require careful deliberation and planning for use. To explore these issues, the Symposium on Exploring Ethical Frontiers of Visual Methods was held at the University of Melbourne, Australia, on 4 March 2014. The symposium was hosted by the Visual Research Collaboratory, a consortium of Australian and Canadian visual researchers, with support from Melbourne Social Equity Institute, University of Melbourne. The symposium represented the culmination of a process to develop a resource outlining principles of ethical practice for visual researchers and ethics committee members, the Guidelines for Ethical Visual Research Methods, which were launched at the event. The Guidelines present a framework for considering ethical matters in visual research, distinguishing six groups of issues united by an overarching theme: confidentiality; minimizing harm; consent; fuzzy boundaries; authorship and ownership; and representation and audiences.